The spirit of creation : modern science and divine action in the Pentecostal-charismatic imagination - Yong, Amos. (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2011)
Is a Pentecostal-charismatic worldview defensible in light of contemporary science? In The Spirit of Creation, Amos Yong demonstrates that Pentecostal thought does indeed have merit in scientific contexts. What's more, he argues that Pentecostal-charismatic views regarding the dynamic presence and activity of the Spirit of God and the pluralistic cosmology of many spirits have something important to add to the broad discussion now taking place at the crossroads of science and religion. Interacting with many scientific fields of study--including psychology, sociology, evolutionary science, cosmology, and more--Yong's Spirit of Creation demonstrates the significance of Pentecostal ideas to the ongoing dialogue between theology and science. --From publisher's description.
The Pentecostal encounter with science : whence and whither? -- The science of Pentecostalism : spirit and interdisciplinarity in theology and science -- The spirit at work in the world : a Pentecostal perspective on the divine action project -- Natural laws and divine redemption : teleology, eschatology, and the activity of the spirit -- Ruach over the primordial waters : a pneumatological theology of emergence -- A spirit-filled creation? Toward a pneumatological cosmology.
Includes bibliographical references and indexes.
Keywords: Religion and science; Pentecostalism -- Doctrines